Comparative Study of effects of Nifedipine and Isosorbide Dinitrate and Their Interaction on Isolated Rabbit Aortic Strips - Afridi, Abdul Hameed; Nasim, Riaz; Khan, Hidayat Hussain; Cheema, Maqsood Ahmad (Journal of Postgraduate Medical Institute, 2011)
Experiments were performed on Isolated Rabbit Aorta in order to study the action of nifedipine and isosorbide dinitrate on noradrenaline-evoked contractions. Contractions of aorta were obtained with increasing concertrations of noradrenaline. The tissue was kept in Krebs physiological salt solution. The effects were recorded with the help of narco Mark IV physiograph (USA). Both nifedipine and isosorbide dinitrate caused a decrease in amlitude of contractions of the aorta. However, none caused 100 percent inhibition of the evoked contractions. Percentage decrease in the amlitude of evoked contractions of the aorta caused by nifedipine was compared with the percentage decrease caused by isosorbide dinitrate. The effects of the combination of nifedipine + isosorb ide dinitrate on the aorta were compared with the effect of the individual test drugs.